Impact of no residual versus residual disease after hysterectomy for stage 1 cervical cancer on recurrence - Ntunja, Sive (Department of Obstetrics and Gynaecology, 2026)
Background: Histopathological risk factors for recurrence of cervical cancer following hysterectomy for stage I disease are well established. The impact of residual disease after LEEP in patients undergoing hysterectomy for stage 1 cervical cancer on recurrence has not been extensively studied. Design and Methods: Records of all patients who underwent hysterectomy for stage I cervical cancer from 1st January 2008 to 31st December 2017 were reviewed. The follow-up period was at least 60 months or until death. Data collected included demographic information, histopathological risk factors, residual disease status on hysterectomy specimen, treatment modalities and recurrence rates. Results: We analysed 147 patients: 55 stage 1A1, 11 stage 1A2, 80 stage 1B1 and 1 with stage 1B2. Median age was 47 (27 – 76) years. All patients had a cervical excision procedure (LEEP OR CKC) for histological diagnosis, followed by simple hysterectomy (29.6%), simple hysterectomy with lymphadenectomy (12.3%) or radical hysterectomy (58.2%). The prevalence of residual disease on hysterectomy specimen was 56.5%, versus no residual disease (43.5%). The overall recurrence rate was 9.5%. Thirty patients received adjuvant radiotherapy, of these, 29 had residual disease, with 6.2% of them developing disease recurrence. The overall survival (OS) and disease-free interval (DFI) were 96.6% and 91.6% respectively. Conclusion: This study found a correlation between presence of residual disease and known histological risk factors, that is size of the lesion and depth of stromal invasion. However, there was no strong correlation between residual disease and lymphovascular space invasion in this study. All patients that had recurrence had residual disease. When excluding those with lymph node metastasis, there were no recurrences in the group with no residual disease.